Devalued and distrusted can the pharmaceutical industry restore its broken image? - LaMattina, John L. (Wiley, 2013)
"While the pharmaceutical industry can play an important role in converting the knowledge generated by the Human Genome Project into new medicines, it also faces a popular perception that it is simply out to make money by promoting unsafe medicines to an unsuspecting public. Written by former Pfizer president John LaMattina, this book addresses the progress that the industry has made in improving its abilities to measure both the risk and benefits of its new medicines, where the industry should invest its R&D resources, and how the industry can rehabilitate its image. Essential reading for pharmaceutical executives and professionals"--